IMMU-19. PD-1 BLOCKADE ACTIVATES CD4 T CELLS AND THE INNATE IMMUNE RESPONSE FOR GLIOBLASTOMA ERADICATION. (5th November 2018) - Speranza, Maria Carmela; Klein, Sarah R; Gokhale, Prafulla C; Wilkens, Margaret K; Jones, Kristen L; Chaudhri, Apoorvi; Kirschmeier, Paul T; Reardon, David; Freeman, Gordon
Abstract: Blockade of immune cell co-inhibitory receptor PD-1 using monoclonal antibodies (mAbs) allows the development of anti-tumor immunity in various solid tumors and lymphoid malignancies. We recently demonstrated that PD-1 blockade elicits an anti-tumor immune response resulting in tumor rejection and long-term survival in approximately 50% of mice with intra-cranial GL-261 glioblastoma, despite the absence of accumulating CD8+ cytotoxic T cells in the tumor or draining lymph nodes. In this investigation, we provide evidence for the role of conventional CD4+ T cells and the innate immune response in PD-1 mediated anti-glioma immunity in this model. In response to anti-PD-1 monotherapy, intratumoral CD4+ T cells, but not CD8+ T cells, expressed significantly elevated levels of IFN-γ and TNF-α pro-inflammatory cytokines and the cytotoxic enzyme, granzyme B. Tbet, GATA3, and EOMES, transcription factors required for T cell proliferation, activation, and effector function, were also up-regulated in CD4+, but not CD8+ T cells in the brains of mice treated with PD-1 mAbs when compared to controls. We demonstrated that depletion of CD4+ or CD8+ T cells, but not NK, was sufficient to completely ablate anti-PD-1-mediated tumor eradication and long-term survival. CD4+ T cell activation was accompanied by the classical activation and M1 polarization of resident microglia and tumor-infiltrating macrophages. Together, these studies demonstrate for the first time a role for CD4+ T cells and the innate immune response in the eradication of glioblastoma by PD-1 blockade.